Targeting Lead in Solid Waste - Hilary Sigman (Rutgers University, Department of Economics, 2003)
This paper explores policy options for reducing lead in municipal solid waste. It focuses on policies that rely on economic incentives, such as taxes, deposit-refunds, and recycled content standards. The paper addresses the relative cost effectiveness of these approaches and also considers the overall desirability of government intervention to reduce lead disposal.
Keywords: 330; Blei; Abfallvermeidung; Umweltschutz; Kosten-Wirksamkeits-Analyse; Vereinigte Staaten